Tasamuh Religion: Study on Simpul Iman Community (SIM-C) - Syayekti, Ela Indah Dwi; Nurrohmah, Shinta; Alghozali, Ahmad Mirshad (Journal of Islamic Communication and Counseling, 2023)
Simpul Iman Community is a forum for interfaith theological dialogue between students of Sanata Dharma University, Duta Wacana Christian University, and Sunan Kalijaga State Islamic University, Yogyakarta. This organization was born as a form of maintaining tolerance and the teachings of compassion from every religion. The purpose of this research is to find out how the forms of interreligious communication that occur in SIM C. This study uses a qualitative approach with an observational method that observes how members of the SIM C organization engage in dialogue. The results of this study indicate that all activities are carried out with the awareness that all human beings can live together based on tolerance and compassion. The content and method of dialogue are not only about theological debates but also about how implementing the teachings and values of divinity in each religion affects life in society. The way SIM C dialogue members do not offend one another. They dialogue tolerantly and do not touch the sensitive side of each religion. It is hoped that this research can be a reflection to create spaces for dialogue between faiths to create harmony in the nation's life.